Synthesis and crystal structure of di-tert-butyl 1″-acetyl-2,2″,9′-trioxo-4a′,9a′-dihydro-1′H,3′H,9′H-dispiro[indoline-3,2′-xanthene-4′,3″-indoline]-1,3′-dicarboxylate, C39H38N2O9 - Li Wu-Wu; Liu Xiong-Li; Li Xiao-Peng; Zheng Hao-Nan; Weng A-Tong; Feng Ling-Ying; Liu Lu (Zeitschrift für Kristallographie - New Crystal Structures)
C39H38N2O9, monoclinic, P21/c (no. 14), a = 9.9846(6) Å, b = 31.4308(13) Å, c = 11.5739(6) Å, β = 110.712(7)°, V = 3397.4(3) Å3, Z = 4, Rgt(F) = 0.0596, wRref(F2) = 0.1221, T = 293 K.